Singing Psalms with owls: a Venda twentieth century musical history - Kruger, Jaco (International Library of African Music, 1999)
World historiography of the second half of the twentieth century has been marked by the expansion of historical subject matter. Bundy (1991:94-95) notes of American historiography that "new methodologies, new sources of evidence, new themes and concepts have not only transformed existing specialist fields of enquiry but also called into being entirely new genres and sub-disciplines”. South African historiography has lagged behind in this respect, and it is only in recent years that themes in social history have emerged. These include demography, the family, youth, old age, death, crime, leisure, health, education and law (Bundy 1991:100). Bundy (1991:99-100) furthermore notes that the study of these themes has not yet been taken far, while "entire areas of the past remain blank”. While artistic cultural forms like literature, orature, graphic and plastic art, theatre, dance and music are receiving increasing historical attention, they too still have to enter mainstream historiography. Furthermore, within the domain of these artistic forms, musical perspectives in particular are inadequately represented in historical reconstruction.
Keywords: African Music